1991
DOI: 10.1136/bjsm.25.4.200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cooling the legs on performance in a standard Wingate anaerobic power test.

Abstract: The possibility that peripheral hypothermia may impair muscular performance in various sports led us to assess the usefulness of the Wingate anaerobic power test in subjects with normal and cooled leg muscles. Using this test without modification, peak power, average power output, and cumulated work to the point of fatigue were all decreased by cooling, although the fatigue index (the declining rate of change of power output) was less. It is concluded that this test could usefully be employed in field studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 5 publications
2
26
0
1
Order By: Relevance
“…Crowley et al (1991) found that in subjects performing a test of maximal power output there was not only the expected profound loss of power when the subjects' legs were chilled by a few degrees Celsius (in agreement with previous reports, e.g. Bergh and Ekblom 1979), but also the cumulated work capacity under these conditions was greatly reduced.…”
Section: Introductionsupporting
confidence: 82%
“…Crowley et al (1991) found that in subjects performing a test of maximal power output there was not only the expected profound loss of power when the subjects' legs were chilled by a few degrees Celsius (in agreement with previous reports, e.g. Bergh and Ekblom 1979), but also the cumulated work capacity under these conditions was greatly reduced.…”
Section: Introductionsupporting
confidence: 82%
“…Most researchers have addressed the effects of local cold treatments, where particular parts of the body were cooled or whole body was immersed in cold water on the level of chosen motor abilities or physical work capacity, under different temperatures [30][31][32][33][34][35][36]. Others evaluated the influence of cooling on the rate of recovery following injuries [19,22,27].…”
Section: Discussionmentioning
confidence: 99%
“…In the conducted research, significant reduction was observed in this variable after the cooling treatment in both sexes, thus it was concluded that single whole body cryostimulation treatment could influence speed endurance significantly in short physical efforts of supramaximal intensity. Crowley et al [29] showed a decrease in maximal anaero bic power, average power, and total external work during a Wingate test after local cooling of the lower limbs. At the same time, he observed a smaller drop in the level of the fatigue index.…”
Section: Discussionmentioning
confidence: 99%
“…A short warmup prior to exercise may effectively diminish the negative effects of whole body cooling by elevating deep muscle temperature, thus confirming the thesis presented ear lier that incorporating a warmup procedure after whole accessible literature. Most scientists have addressed the effects of local cryotherapy treatments, where particu lar parts of the body were cooled, on the level of chosen motor abilities or physical work capacity, under different temperatures [18,[28][29][30][31][32][33]. Other authors evaluated the in fluence of local cooling on the rate of recovery following injuries [20,22,24].…”
Section: Discussionmentioning
confidence: 99%